2011
DOI: 10.1002/humu.21633
|View full text |Cite
|
Sign up to set email alerts
|

Somatic mutations in the chromatin remodeling gene ARID1A occur in several tumor types

Abstract: Mutations in the chromatin remodeling gene ARID1A have recently been identified in the majority of ovarian clear cell carcinomas. To determine the prevalence of mutations in other tumor types, we evaluated 759 malignant neoplasms including those of the pancreas, breast, colon, stomach, lung, prostate, brain and blood (leukemias). We identified truncating mutations in 6% of the neoplasms studied; non-truncating somatic mutations were identified in an additional 0.4% of neoplasms. Mutations were most commonly fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
226
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(243 citation statements)
references
References 25 publications
11
226
0
6
Order By: Relevance
“…In gastric cancer, an association has been described between MSI and mutations in ARID1A. 12,[14][15][16] As the rate of somatic ARID1A mutations in MSI cases was 12-to 61-fold higher than the global background mutation rate, it was suggested that the ARID1A gene is particularly targeted by MSI. 12 A possible association between ARID1A loss and MSI, as has been reported for gastric cancer, has not been studied in endometrial cancer.…”
mentioning
confidence: 99%
“…In gastric cancer, an association has been described between MSI and mutations in ARID1A. 12,[14][15][16] As the rate of somatic ARID1A mutations in MSI cases was 12-to 61-fold higher than the global background mutation rate, it was suggested that the ARID1A gene is particularly targeted by MSI. 12 A possible association between ARID1A loss and MSI, as has been reported for gastric cancer, has not been studied in endometrial cancer.…”
mentioning
confidence: 99%
“…[5][6][7] Mutations in various subunits of the SWI/SNF can influence the epigenetic regulation of genes and have been identified in different cancers in recent years. 5,6 Since the two reports on ARID1A in 2010, high frequencies of mutations in the ARID1A gene and loss of ARID1A protein have been reported in endometrial cancer (26-37%), 8,9 adenocarcinoma of the cervix (32%), 10 gastric cancer (10-14%), 9,11 anaplastic thyroid cancer (14%), 9 colorectal cancer (10%), 11 breast cancer (64%) 12 and several cancer cell lines. ARID1A mutations seem, although also present in other tumor types, predominantly linked to gynecological and in particular endometriumrelated tumors.…”
mentioning
confidence: 99%
“…Grasso et al 47 also described a frequent copy number loss on chromosome 5q21 at the location of CHD1, a gene encoding a chromatinremodeling enzyme, and documented loss or mutation in multiple chromatin-remodeling genes, as has been found for multiple tumor types. 47,[52][53][54] They documented that multiple of these chromatinmodifying genes directly interact with the androgen receptor and along with additional regulators, such as FOXA1, can partially explain the androgen-resistant nature of the tumors they sequenced.…”
Section: Somatic Alterations In Tumorsmentioning
confidence: 99%